DESCRIBING TEACHERS’ STRATEGIES IN TEACHING ENGLISH VOCABULARY - Ine Magfira M Keo; Sriati Usman; Mawardin M Said (Tadulako University, 2021)
This is a qualitative research. Its aims are to find out teachers’ strategies in teaching English vocabulary and to identify the obstacles faced by teacher in implementing the strategies. The research method applied by researcher is qualitative. The data were taken from interview with English teachers at SMA Negeri 1 Ampana and analyzed by using descriptive analysis. The result of the research revealed some strategies applied by teacher to teach English vocabulary includes: 1) Comprehending Vocabulary through Reading and Translating Text; 2) Memorizing Vocabulary; 3) Dictionary Use. The teacher uses those strategy in increasing students’ vocabulary mastery. Based on the interview, the teacher faced some problems in teaching vocabulary. The problem derived from students, such as lack of motivation, the students sometimes feel lazy, bored and some of students become crowded in learning. They also quickly amd easily forget the vocabulary that has been learnt before because they do not practice it at home.